RECOPTIC APPLICATION DEVELOPMENT WITH ARTIFICIAL INTELLIGENCE ON DRUG DETECTION FEATURE FOR VISUALLY IMPAIRED PEOPLE - Annisa Umulfath; Abdurrahman; Ahmad Mawardi Hakim; Muhammad Haikal; Manfred Michael; Guntur Eka Saputra (International Journal Science and Technology, 2023)
Recoptic application is an optical recognition application. This application is equipped with TalkBack and the application of artificial intelligence so that the camera on the smartphone can detect and provide information about drugs, text, and objects. Recoptic is currently implemented on Android smartphones and applies the image-to-text converter technology with Optical Character Recognition (OCR). The camera can detect the text on the drug cover and the type of drug, and the application will read out the information with TalkBack. Recoptic has been tested with a user acceptance test (UAT) from experts in medical disciplines and potential users, namely blind people. Features in the application include a voice to guide users and drug detection to read and provide information with sound, objects, and text. The application has been tested and received input with the user acceptance test (UAT) method from experts and blind users. Based on the test results and data collected, as many as 923 drugs have been acquired, and the resulting more than 80% UAT is considered successful for the subject by blind people. Recoptic is implemented on Android-based smartphones.